LITERASI MEDIA DALAM MENGHINDARI INFORMASI HOAX PADA SISWA SMAN 5 KOTA SUKABUMI - Umban Adi Jaya; Hilda Sri Rahayu; Cucu Hodijah; Hasti Pramesti Kusnara (LPPM Universitas Bina Bangsa, 2024)
In Indonesia, social media has become one of the most popular platforms among young people. However, the high use of social media is not balanced with awareness of the negative impacts it can have, one of which is hoaxes. Hoaxes, disinformation and misinformation are often discussed in the digital world and on media internet, and it can be said that the spread of hoaxes in Indonesia is influenced by low digital literacy. Many people are not yet fully aware of the impact of media on various life contexts. Responding to this phenomenon, a team from the Indonesian Wiyata Management Institute and Ma'soem University held community service regarding social media literacy training related to hoax prevention for high school students in Sukabumi Regency. The aim of this community service is to increase knowledge and awareness regarding the impact of social media, especially to provide awareness of the importance of social media. In this community service, the approach used is lecture and discussion